The language as the base of civilization - Iskakova, Sh. G.; Apieva, A. E. (ЗКАТУ им. Жангир хана, 2018)
The article proves methodic efficiency of debate as one of interactive methods for contemporary education in higher education. It is shown in the article that discussion as a cognitive and argument method integrates techniques of such interactive education methods as case study, collective solution of creative tasks, heuristic conversation, and brainstorming. Debate is represented in the article as one of the varieties of this method. Debate supposes the formulation of an alternative point of view and concludes with arriving at a group decision.В статье обосновывается методическая продуктивность дискуссии как одного из интерактивных методов современного образования в высшей школе. Показано, что дебат как способ познания и способ ведения спора интегрирует в себе приемы и техники таких методов интерактивного обучения, как кейс-метод, метод коллективного решения творческих задач, беседа, метод мозгового штурма.
"Роль молодежи в развитии науки и инновации в ХХІ веке" в рамках программы "Рухани жаңғыру", посвящ. 20-летию столицы Республики Казахстан - города Астаны "Ел жүрегі - Астана" и 55-летию Западно-Казахстанского аграрно-технического университета имени Жангир хана: мат. третьей респ. науч.-практ. конф. студентов и магистрантов
Keywords: рк; конференции; отечественное издание; республиканская конференция; педагогика; дебаты; интерактивное обучение; дискуссии; методы обучения